2002
DOI: 10.1191/0961203302lu144oa
|View full text |Cite
|
Sign up to set email alerts
|

Scleroderma-like nailfold capillaroscopic abnormalities are associated with anti-U1-RNP antibodies and Raynaud's phenomenon in SLE patients

Abstract: This study aimed to evaluate the association between nailfold capillary abnormalities and the presence of Raynaud's phenomenon (RP), anti-U1-RNP, and anti-cardiolipin (aCL) antibodies in SLE patients. One-hundred SLE patients were studied. Widefield nailfold capillaroscopy was considered abnormal according to five criteria. Intercapillary distance, capillary width and capillary length were registered by videomorphometry in two fingers in 100 patients and in four fingers in 40 of these patients. Both the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
1
11

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 26 publications
5
54
1
11
Order By: Relevance
“…In a study with children and adults, the SLEDAI and presence of anti-RNP antibodies were associated with changes on NFC. 25 In our study the four patients positive for anti-RNP showed no changes on NFC.…”
Section: Discussionsupporting
confidence: 41%
“…In a study with children and adults, the SLEDAI and presence of anti-RNP antibodies were associated with changes on NFC. 25 In our study the four patients positive for anti-RNP showed no changes on NFC.…”
Section: Discussionsupporting
confidence: 41%
“…It is better detected by capillaroscopy. Nailfold telangiectasias in SLE patients were associated with anti-U1RNP antibodies [77]. In addition, telangiectasias and erythema of the nailfold were found in 76% of patients who hadboth DLE and SLE, but none in patients with DLE in the absence of SLE, suggesting that this is a rather sensitive indicator for systemic disease activity [78].…”
Section: Periungual Telangiectasiasmentioning
confidence: 99%
“…It is not unusual, for example, that a patient with SLE presents isolated features suggestive of systemic sclerosis, such as swollen fingers, Raynaud's phenomenon, and esophageal dismotility (Furtado et al 2002). In some cases, there is concomitant full-blown presentation of two or more of these conditions.…”
Section: Table Imentioning
confidence: 99%